Turismo e patrimônio cultural: políticas, ações e intervenções no município de Natal-RN - Morais, Luciléia Lima de (2016)
The main objective of the study is to understand the factors that have hampered the functionalisation of the historical center of Natal between 1976 and 2015, during which time relevant public policies for the preservation of the Brazilian cultural heritage were elaborated to cultural valurization. The methodology of the work was based on the analysis of the main actions and policies of tourism and culture that occurred in the historic center in order to understand whether or not there is an intersection between public policies and reflect on the deliberate actions of the various actors present in the historical region of the city. Interviews were conducted with representatives of local government, private sector, civil society and tourists through unstructured interviews. This is a cross-sectional, descriptive and exploratory study, where the content analysis technique was selected for the treatment of the data. It was noticed that preservation actions, although contemplating in their objectives the promotion of tourist activity in historical centers, can not transpose the inventory and diagnostic phase or are restricted to the implementation of projects in isolation and without continuity, partaking in stages considered preliminary in the evaluation of public policies. It was also observed that there is no tourism management of cultural heritage and there is no specific action of tourist promotion of the cultural corridor of Natal as it is carried out with the segment of sun and beach. The area is already endowed with sufficient projects for its historical, tourist and cultural valorization, however, the conflict of interest between the preservation agencies and other secretariats, the bureaucracy and the lack of knowledge of the specific legislation by the formulators of actions in the region historic are still the main obstacles to the tourist function in the historical center of Natal.